COMPETITIVE ADVANTAGE UDANG WINDU PINRANG DALAM PERDAGANGAN INTERNASIONAL - Riska Luneto; Kaslam (UIN ALAUDDIN MAKASSAR, 2022)
Indonesia is one of the countries that has potential for fisheries and marine resources, this of course has a positive value for state revenue. One of the commodities that play an important role is tiger prawns which are spread in almost all parts of Indonesia, Pinrang Regency is one of them. Responding to global demand that continues to increase, efforts are made by stakeholders to meet demand, cooperation, renewal and renewable technology are structured as a form of increasing production levels and productivity. This study uses the diamond model concept, Michael Porter in looking at the competitive advantage of Indonesian tiger prawn commodities, the author tries to map the value of competitiveness and superiority of Indonesian tiger shrimp products, especially tiger shrimp in Pinrang Regency.